PENGARUH MOTIVASI DAN SIKAP WISATAWAN NUSANTARA TERHADAP PEMBELIAN PRODUK WISATA BAHARI DI TANJUNG BENOA PADA MASA PANDEMI COVID-19 - Fitriadi, Muhammad Dio; Wijaya, NMS.; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 1 (2022): Jurnal IPTA (July 2022)DO - 10.24843/IPTA.2022.v10.i01.p06, 2022)
The decline in the number of tourists related to the current Covid-19 pandemic situation has made marine tourism bussiness offering tourism product to attract tourist visiting Bali, especially Tanjung Benoa. The number offers provided by marine tourism businesses to tourist makes companies need to analyze the effect of motivation and attitudes of domestic tourist purchasing descision on marine tourism product during covid-19 Pandemic in Tanjung Benoa.  This research was conducted online to domestic tourists who had purchased marine tourism products in Tanjung Benoa in the last 1 year during the pandemic. The sample in this study was selected using the theory of Hair, et al (2006) with the number of respondents are 75 tourists. Data were collected through an online questionnaire, and then analyzed using multiple linear regression using the SPSS version 21.0 program. The results of this study are motivation (X1) has a significant effect on purchasing decisions (Y), attitudes (X2) have a significant effect on purchasing decisions (Y), also motivation (X1) and attitudes (X2) simultaneously affect purchasing decisions (Y) on marine tourism products in Tanjung Benoa.